2011
DOI: 10.1111/j.1447-0756.2010.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of menstrual pain and associated risk factors among Iranian women

Abstract: Aim:  To estimate the prevalence of dysmenorrhea in Iranian women and investigate associated risk factors. Material & Methods:  In a cross‐sectional study in Tehran, Iran in 2007, 381 women (81% response rate, age 16–56 years) were selected through a stratified random sample of 22 different districts and completed a questionnaire about dysmenorrhea. Descriptive statistics, spearman rank correlation statistic, and ordinal logistic regression models were used. Confounding and effect‐modification were explored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
97
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 35 publications
16
97
1
4
Order By: Relevance
“…It was not possible to discriminate between primary and secondary dysmenorrhoea by questionnaire, and menstrual pain as a whole was considered in this study. In this study higher socio-economic status women had less pain compared with women from low socio-economic status which is in line with a study done among Iranian women in 2007 (24). All the association does not necessarily imply a causal relationship as per epidemiological study (25).…”
Section: Discussionsupporting
confidence: 78%
“…It was not possible to discriminate between primary and secondary dysmenorrhoea by questionnaire, and menstrual pain as a whole was considered in this study. In this study higher socio-economic status women had less pain compared with women from low socio-economic status which is in line with a study done among Iranian women in 2007 (24). All the association does not necessarily imply a causal relationship as per epidemiological study (25).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, the reported rate was more appropriately interpreted as one-month prevalence rate. The highest prevalence of 91% was reported in a random sample of Iranian women aged 16 to 56 years, with most under 30 years of age without children, through self-reporting [72].…”
Section: Prevalence And/or Incidencementioning
confidence: 99%
“…The association of age and dysmenorrhea was reported in nine studies, with two longitudinal [11,69] and five cross-sectional [3,65,68,71,72] studies consistently demonstrating a significant inverse relationship between age and the risk of dysmenorrhea (Table 3-2). Among the seven studies reporting an inverse association, four conducted the analyses adjusted for parity/live birth, whereas the other three failed to do so [69,71,72]. In the study by Weissman et al [11], the univariate analysis revealed that women younger than 25 years were at more than twice the risk [76].…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations